2020
DOI: 10.1186/s40644-020-00309-y
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of brain metastases: low-risk metastasis areas may be avoided when treating with whole-brain radiotherapy

Abstract: Objective: Previous work has demonstrated that metastases are not uniformly distributed across the brain. This study aims to determine there are low-risk brain metastasis (BM) areas that may be avoided during whole-brain radiotherapy (WBRT) to reduce neurocognitive toxicity. Methods: Clinical and magnetic resonance imaging (MRI) data of 991 metastases in 192 patients with advanced cancer were analyzed retrospectively. Eleven anatomically defined regions of interest (ROIs) were contoured, and the locations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…The expected rate of BMS in each brain area was calculated as a proportion of brain area volume to total brain volume. Through comparison, we found that the observation frequency of cerebellum was significantly higher than the expected frequency ( P = 9.80 ×10 −15 ), while the observation frequency of temporal lobe, frontal lobe and occipital lobe was significantly lower than the expected frequency, and the difference of temporal lobe was more significant ( P = 1.65 ×10 −4 ), which was similar to the results of previous studies on heterogenous primary pathological type of brain metastases [ 11 , 13 , 32 ]. In order to make the research more thorough, more detailed atlas was applied to the segmentation.…”
Section: Discussionsupporting
confidence: 88%
“…The expected rate of BMS in each brain area was calculated as a proportion of brain area volume to total brain volume. Through comparison, we found that the observation frequency of cerebellum was significantly higher than the expected frequency ( P = 9.80 ×10 −15 ), while the observation frequency of temporal lobe, frontal lobe and occipital lobe was significantly lower than the expected frequency, and the difference of temporal lobe was more significant ( P = 1.65 ×10 −4 ), which was similar to the results of previous studies on heterogenous primary pathological type of brain metastases [ 11 , 13 , 32 ]. In order to make the research more thorough, more detailed atlas was applied to the segmentation.…”
Section: Discussionsupporting
confidence: 88%
“…However, other tumors have been described such as carcinoma, blastoma, craniopharyngioma, germ cell tumors, mesenchymal tumors, and secondary tumors. The sellar region is known as a low‐risk brain metastasis area 2 . The prevalence of pituitary metastasis represents 1% of all surgical tumors of the pituitary gland 3 .…”
Section: Introductionmentioning
confidence: 99%
“… 3 Current National Comprehensive Cancer Network guidelines recommend a combination of surgery, radiosurgery, whole-brain radiotherapy (WBRT), and/or systemic therapy for the treatment of brain metastasis. 4 Treatment choice for brain metastasis is based on pathology, number and size of metastases, and location of the metastatic lesion. Surgery and/or radiosurgery has historically been more appropriate for patients with a surgically accessible or few brain metastasis while WBRT is often used for those with numerous lesions, though continued research into the effectiveness of these treatments is still being performed.…”
mentioning
confidence: 99%
“…Surgery and/or radiosurgery has historically been more appropriate for patients with a surgically accessible or few brain metastasis while WBRT is often used for those with numerous lesions, though continued research into the effectiveness of these treatments is still being performed. 4 …”
mentioning
confidence: 99%
See 1 more Smart Citation